Satisfaction Among International Student-Athletes Who Participate in the National Collegiate Athletic Association - Trendafilova, Sylvia; Hardin, Robin; Kim, Seungmo (Journal of Intercollegiate Sport, 2010)
The number of international student-athletes participating in the National Collegiate Athletic Association (NCAA) has nearly doubled from 8,945 in 2001–02 to 16,440 in 2007–08 (DeHass, 2009). As a result of such dramatic growth in the number of student-athletes participating in NCAA athletics, it is important to understand the level of satisfaction among this group. Determining whether athletes are satisfied with their experience may aid in recruiting future international athletes as well as potentially leading to higher retention and graduation rates. Thus, the purpose of this study was to explore the level of satisfaction (academic and athletic) among international student-athletes who participate in NCAA Division I-Football Bowl Subdivision athletics. Data analysis revealed that international student-athletes are satisfied with the dimensions measuring satisfaction, including academic support services, personal treatment, team social contribution and medical support. In addition, male athletes are more satisfied with external agents (i.e., media, the local and university community) than female athletes. These findings will not only help coaches and administrators better understand international student-athletes’ academic and athletic experience in the United States, but will also contribute to their understanding of the factors leading to an increased level of satisfaction. Providing the best possible environment to achieve high level of satisfaction ultimately will lead to a better performance on and off the field (Zhang, DeMichele & Connaughton, 2004).